Photocatalytic activity of enlarged microrods of α-Bi2O3 produced using ethylenediamine-solvent. Issue 10 (1st August 2016) - Hernández-Gordillo, Agileo; Medina, Juan C.; Bizarro, Monserrat; Zanella, Rodolfo; Monroy, B.M.; Rodil, Sandra E.
Abstract: Microrods of α-Bi2 O3 were prepared by a simple chemical precipitation method, replacing the hydroxyl (OH − ) ions by the ethylenediamine-solvent as both a precipitating and capping agent; it can also function as a morphological template. The influence of the ethylenediamine solvent concentration on the crystalline structure, optical properties, morphology, and photocatalytic activity was investigated. The prepared samples were characterized by X-ray diffraction, diffuse reflectance spectroscopy, scanning electron microscopy, Fourier transformed IR analysis, thermal analysis and photoluminescence spectroscopy. The adsorption capacity in dark conditions and the photocatalytic activity under UV-light were studied as a function of the photocatalyst load by using indigo carmine dye solution. The highest photoactivity was observed for the non-agglomerated Bi2 O3 microrods obtained with ethylenediamine-solvent at 40 vol%. The photocatalytic mechanism was discussed as a function of surface oxygen vacancies generated along to the microrod surface caused by the ethylenediamine-solvent.